Rapid and Sensitive Detection of Meloidogyne graminicola in Soil Using Conventional PCR, Loop-Mediated Isothermal Amplification, and Real-Time PCR Methods - He, Qingcong (Plant disease, 2021)
Meloidogyne graminicola is one of the major plant-parasitic nematodes (PPNs) that affect rice agriculture. Rapid identification and quantification of M. graminicola in soil is crucial for early diagnosis so that measures can be taken to reduce the impact of PPN diseases and ensure food security. In this study, M. graminicola species-specific primers for conventional PCR, loop-mediated isothermal amplification (LAMP), and real-time PCR were designed based on the sequence-characterized amplified region. The primers were highly specific and sensitive, and only samples containing M. graminicola DNA showed positive results. The sensitivity of LAMP and real-time PCR (two second-stage juvenile [J2] M. graminicola in 100 g of soil) was higher than that of conventional PCR (200 J2s in 100 g of soil). A standard curve (correlation coefficient R2 = 0.970, P < 0.001) was generated by amplifying DNA extracted from 0.5 g of soil, and a significant correlation was observed between the number of M. graminicola determined by microscopic examination and that predicted from the standard curve (R2 = 0.477, P = 0.0160). In quantification analyses of M. graminicola isolated from 31 naturally infested soils, the sensitivity of LAMP and real-time PCR (22 M. graminicola in 100 g of soil) was higher than that of conventional PCR (211 M. graminicola in 100 g of soil). The conventional PCR, LAMP, and real-time PCR methods have the potential to provide a useful platform for rapid species identification according to the experimental conditions. The real-time PCR assay and standard curve can be used for quantification of M. graminicola. These newly developed assays will help to facilitate the control of these economically important PPNs